Peran Guru Pendidikan Agama Islam dalam Menanggulangi Kenakalan Peserta Didik - Ana Maulida; Rini Rahman (An-Nuha, 2022)
This study was conducted to determine the reality of student delinquency, to determine the factors causing student delinquency, and to describe the efforts of Islamic Religious Education teachers in tackling student delinquency. The method used in this study is a qualitative method with a phenomenological approach. Data was sourced from interviews with the Principal, Deputy Principal for Student Affairs, PAI teachers, and Counseling Guidance teachers. The results showed that the reality of delinquency in SMP Negeri 6 Bukittingi students was divided into 3 levels, the first being mild delinquency, for example coming late to school, dressing untidily, leaving class during PBM, and not doing assignments. Second, delinquency that disturbs the peace and security of others and sexual delinquency, for example, speeding on the street, fighting, noisy during PBM, and smoking. Third, sexual delinquency, for example, dating and socializing knows no boundaries. The causes of student delinquency there are three factors, namely: family environment, school, and community. The efforts of Islamic Religious Education teachers in tackling student delinquency are preventive, repressive, and curative actions.